PEMBATASAN TIKTOK SHOP MENURUT PERATURAN MENTERI PERDAGANGAN NOMOR 31 TAHUN 2023 TENTANG PERIZINAN BERUSAHA, PERIKLANAN, PEMBINAAN, DAN PENGAWASAN PELAKU USAHA DALAM PERDAGANGAN MELALUI SISTEM ELEKTRONIK - Margareta, Linda (Universitas 17 Agustus 1945 Samarinda, 2025)
ABSTRACT. TikTok Shop has grown tremendously since it was first introduced, offering ease for users to make transactions without having to leave the TikTok app. Regulation of the Minister of Trade Number 31 of 2023 provides restrictions on TikTok Shops, which are very important in maintaining healthy competition. The restriction stipulates that social media does not function as a direct seller, but only as a platform to facilitate transactions between sellers and buyers. This study analyzes the implementation of TikTok Shop restrictions according to the Regulation of the Minister of Trade Number 31 of 2023 on e-commerce business actors. and restrictions on the prohibition of social media from becoming direct sellers in the Regulation of the Minister of Trade Number 31 of 2023 have been effective in creating a healthy e-commerce ecosystem. The implementation of TikTok Shop restrictions according to the Regulation of the Minister of Trade Number 31 of 2023 has had a significant impact on e-commerce business actors in Indonesia. These restrictions, which govern business licensing obligations, TikTok's prohibition on being a direct seller, and transaction supervision, aim to create a healthy and fair e-commerce ecosystem. The government should strengthen the oversight mechanism for large e-commerce platforms, such as TikTok, by utilizing adequate technology and human resources. And for the government to strengthen the oversight mechanism for large e-commerce platforms, such as TikTok, by utilizing adequate technology and human resources. Keywords: E-commerce, TikTokShop Restrictions, Legal Protection.